UPAYA INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM PADA PESERTA DIDIK MELALUI PROGRAM UNGGULAN SEKOLAH (STUDI KASUS DI KELAS IX MTS ALMAARIF 02 SINGOSARI) - Hanna Rizmania; Arief Ardiansyah; Moh Muslim (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Moral decadence is a problem in society, especially for students in this modern era.Students need a strong understanding and a continuous process in instilling PAI values. The focus of this research: 1) How is the process of internalizing PAI values to students through the flagship program at Mts Almaarif 02 Singosari? 2) What are the PAI values that are internalized to students through the flagship program at Mts Almaarif 02 Singosari? 3) What are the supporting factors and inhibiting factors in efforts to internalize PAI values to students through the flagship program at Mts Almaarif 02 Singosari?. The research method uses qualitative case studies, with interview, observation, and documentation techniques. Analyzed by data condensation, data presentation, data withdrawal or verification of conclusions. Checking the validity of the data with the testcredibility, transferability, dependability, and confirmability. The end result: 1) The process of internalizing PAI values to students through the flagship program of MTs Almaarif 02 Singosari, contains 3 things, namely the strategy stage, the value internalization stage, and the method of internalizing PAI values. 2) PAI values that are internalized include the values of faith, worship, and morals. 3) Supporting factors, namely the comfort of the situation and condition of the place, as well as the completeness of the facilities. The inhibiting factor is the disgraceful behavior of students and guardians of students who do not pay attention to their children in worship or other matters.